ASSESSMENT OF THE IMMUNOGENICITY AND SAFETY OF 23-VALENT POLYSACCHARIDE PNEUMOCOCCAL VACCINE IN PATIENTS WITH RHEUMATIC DISEASES - M. S. Naumtseva; B. S. Belov; E. N. Aleksandrova; G. M. Tarasova; A. A. Novikov; D. E. Karateev; E. L. Luchikhina; A. V. Volkov; N. N. Yudkina; O. A. Antelava; A. N. Khelkovskaya-Sergeeva; M. V. Cherkasova; et al. (Научно-практическая ревматология, 2016)
Objective: to investigate the immunogenicity and safety of 23-valent polysaccharide pneumococcal vaccine in patients with rheumatic diseases (RD).Subjects and methods. The prospective open-label comparative study enrolled 133 people (102 (76.7%) women and 31 (23.3%) men) aged 23 to 76 years, including 79 patients with rheumatoid arthritis (RA), 16 with systemic sclerosis, and 7 with dermatomyositis/polymyositis, as well as 31 subjects without systemic inflammatory RD (a control group), who had a recent history of at least two cases of lower respiratory tract infections (bronchitis, pneumonia). At their inclusion, all the patients with RD were receiving ant-inflammatory therapy, including 52 taking methotrexate (MT), 14 – leflunomide (LEF), and 13 – MT + tumor necrosis factor-α (TNF-α) inhibitors. The 23-valent polysaccharide pneumococcal vaccine Pneumo-23 (Sanofi Pasteur, France) was administered in a single dose of 0.5 ml subcutaneously during continuous MT or LEF therapy for the underlying disease or 3–4 weeks before the use of TNF-α inhibitors. Clinical examinations of the patients and conventional laboratory studies were performed during control visits (1, 3, and 12 months after vaccination). The serum levels of anti-pneumococcal capsular polysaccharide antibodies were measured in 102 patients by enzyme immunoassay using commercial VaccZymeTM Anti-PCP IgG Enzyme Immunoassay kits (The Binding Site Group Ltd, United Kingdom).Results and discussion. No clinical and radiological symptoms of pneumonia were recorded in any case during the follow-up period of 12 months. The patients with RD and the control group showed a significant, more than double increase in anti-pneumococcal antibodies 12 months following vaccination. Vaccination was well tolerated: 90 (68%) patients displayed no adverse events; 37 (28%) had pain, cutaneous swelling and hyperemia up to 2 cm in diameter at the site of injection for vaccination;6 (4%) had low-grade fever. There were no episodes of a RD exacerbation or any new autoimmune disorders during the follow-up period.Conclusion. The findings were suggestive of the sufficient immunogenicity and good tolerability of 23-valent pneumococcal vaccine in patients with RD.